Brazilian Spotted Fever: the importance of dermatological signs for early diagnosis - Daíne Vargas Couto; Marcelo Zanolli Medeiros; Gunter Hans Filho; Alexandre Moretti de Lima; Aline Blanco Barbosa; Carolina Faria Santos Vicari (Sociedade Brasileira de Dermatologia, 2015)
Brazilian spotted fever is an acute febrile infectious disease caused by Rickettsia rickettsii, transmitted by tick bite. As this disease is rare and has high mortality rates in Brazil, the clinical aspects and epidemiological data may help the diagnosis. We report a case of Brazilian spotted fever in a 19-year-old patient who presented maculopapular exanthema in the palmar region and upper limbs, lymphadenopathy, fever, chills, headache, conjunctival hyperemia, nausea, vomiting, dyspnea, myalgia, developing neurological signs and abdominal pain. He was treated with doxycycline with clinical improvement. We emphasize the importance of the recognition of this disease by dermatologists as cutaneous manifestations are the key findings to establish early diagnosis and prevent complications.